Penile Reinnervation - Oliveira Neto, Fausto Viterbo de; Menezes Neto, Balduino Ferreira de; Magnani, Lucas Vannuchi (Springer Nature, 2025)
Erectile dysfunction (ED) is a multifactorial disease that causes several psychosocial problems. For cases in which pharmacological treatment fails, the penile reinnervation procedure has proved to be a great option. In this surgery, two sural nerve grafts make a bridge of axons from the femoral nerve to the dorsal nerve of the penis and the corpora cavernosa.